Stosunki cywilnoprawne między zjednoczeniem a przedsiebiorstwem państwowym: [Civil law relations between industry association and state enterprise] (Studia Prawnicze / The Legal Studies, 1964)
The problems that determine the legal relations between an industry association acting as a parent organization and state enterprises grouped in it are diverse and comprehensive, but this article considers only one of the questions, namely, whether and to what extent these relations can have civil law nature. This question is so important since one of the main features of civil law relations is the equality of the parties; therefore, this kind of such relations leaves an imprint on the nature of the ties between the association and the enterprise and, to a certain extent, reflects the independence of state enterprises.The study is based on the analysis of the normative acts as a fundamental research material; not only a comprehensive interpretation of the topic in terms of other legal disciplines is needed for the implementation of the future synthesis, but also further research is required to establish the practice that has emerged in connection with the application of the analysed normative acts.Since 1958, the parent organizations in relation to state enterprises have become the so-called industry associations replaced the previously existing central departments (or simply departments) which have been organizational units in the state administration bodies.The institution of associations was introduced gradually, and only in 1960 it obtained the form of a legal but still very generalized regulation according to the Decree on state enterprises. In addition to this Decree, this article highlights a number of normative acts concerning both the organization of associations and their financial system in order to find an answer to the question whether they provide for civil law relations between an association and an enterprise. As a result of the analysis, we can conclude that, although the legal foundations for such an order of relations have been created, and since the association is an economic organization with the rights of a legal entity acting on a self-financing basis, the provisions of the law exclusively provide for the existence of ties the civil law nature of which cannot raise doubts. In principle, the normative acts regulate relations of administrative-legal or financial-legal nature leaving open the question of the legal qualification of non-directive relations, especially in the area of various association services for trusted enterprises (for example, in the area of marketing and supply operations). According to the author, there are no grounds to judge the presence of a corporate element in the structure of an association based on the institution of the so-called association board which includes, in particular, the directors of trusted enterprises and has a decisive vote on some issues. It also does not seem possible to consider, with a few exceptions, an association as a representative of subordinate enterprises according to the civil law. Exactly the same picture is obtained on the basis of the analysis of the articles of associations which are predominantly general and stereotyped.In addition to the regulations on associations, the author analyses the provisions of the law regarding the so-called leading enterprises which can perform all, most or only some of the functions of associations. Particularly noteworthy are the so-called sponsored enterprises which, hypothetically speaking, are much more likely to have civil law relations, since the ties between them and cooperating enterprises are largely devoid of directive elements. However, the provisions of law do not contain an unambiguous answer regarding the legal nature of the legal relations arising in connection with the activities of sponsored enterprises.In conclusion, the author considers the institution of the so-called industrial agreements which represent the current basis for industrial coordination. The organizational unit that carries out this coordination is the so-called leading associations which are associated with the parties to the industrial agreements. Regarding the disputed issue of whether an industrial agreement should be considered a civil law contract or an institution of administrative law, the author favours the second solution specifying that the sanctions provided for by the law for non-fulfilment of the agreement, as well as the method of resolving possible disputes, do not solve the issue of whether and to what extent the implementation of the industrial agreements are on the basis of civil law. In this regard, the need for a thorough analysis of existing agreements and practices related to their implementation is felt with particular force, because only the material obtained in this way could provide a basis for judging the extent to which the civil law relations apply during the implementation of the industrial coordination having great economic importance.